Phytochemical screening and evaluation of anti-oxidant, anti-inflammatory and anticancer activities of leaves of Vernonia amygdalina, Otostegia integrifolia, and Salvia rosmarinus - Mosisa Dejene; Aman Dekebo; Kero Jemal; H. C. Ananda Murthy; S. Giridhar Reddy (Green Chemistry Letters and Reviews)
This study assessed leaves extract from Vernonia amygdalina, Otostegia integrifolia, and Salvia rosmarinus plants for their phytochemical content and in-vitro antioxidant, anti-inflammatory, and anti-cancer activities. The DPPH bioassay for antioxidants, MTT bioassay for anticancer, measurement of the inhibition of albumin-denaturation, and anti-proteinase for anti-inflammatory activities methods were used. The result of phytochemical-screening tests confirmed the presence of alkaloids, steroids, terpenoids, flavonoids, tannins, and saponins in plants. The three plants exhibited IC50 (μg mL−1) for radical – scavenging activities at a concentration 10–30 μg mL−1 which was higher than that of the positive control ascorbic acid. Chloroform/methanol (1:1) S. rosmarinus leaves extract showed the highest anti-inflammatory activity against albumin-denaturation with an IC50 value of 0.58 μg mL−1, followed-by chloroform/methanol (1:1) V. amygdalina leaves extract with an IC50 value of 0.81μg mL−1 [positive control aspirin (IC50 value of 4.59 μg mL−1)]. Both plants’ chloroform/methanol (1:1) extracts demonstrated higher inhibitory activity against proteinase than aspirin. The three plants were tested for anti-cervical-cancer activity at 1250 μg mL−1 concentration. All the plants showed the strong anti-proliferative effects on continuous cell culture of HeLa cells line. The plants that were studied scientifically have provided support for the traditional-therapists’ claim of anticancer activity.